1998
DOI: 10.1128/aac.42.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacies of Three Fluoroquinolone Antimicrobial Agents, Given as Continuous or Pulsed-Water Medication, againstEscherichia coliInfection in Chickens

Abstract: This study compared the efficacy of continuous or pulsed-water medication with enrofloxacin, danofloxacin, and sarafloxacin in eight groups of 90 chicks each by using an infectious bronchitis virus-Escherichia coli model of colisepticemia. The model produced lesions of typical those occurring in birds with severe colisepticemia; for the infected, nonmedicated birds the mortality was 43.5% and the morbidity was 89%, 17.8% of birds had severe lesions, and the birds had a mean air sac lesion score of 2.58. This e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…23 A previous study involving experimentally infected chickens reported that the clinical usefulness of ERFX was superior to DNFX. 2 The AUC:MIC and C max :MIC ratios have been shown to have a particular ability in determining the optimal activity of fluoroquinolones. 13 Our calculated AUC:MIC and C max :MIC ratios support the observation that ERFX is more suitable for the treatment of avian colibacillosis than DNFX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A previous study involving experimentally infected chickens reported that the clinical usefulness of ERFX was superior to DNFX. 2 The AUC:MIC and C max :MIC ratios have been shown to have a particular ability in determining the optimal activity of fluoroquinolones. 13 Our calculated AUC:MIC and C max :MIC ratios support the observation that ERFX is more suitable for the treatment of avian colibacillosis than DNFX.…”
Section: Discussionmentioning
confidence: 99%
“…Although fluoroquinolones are classified as concentration-dependent drugs, Charleston et al reported similar efficacies of continuous and pulsed regimens and suggested that the duration of exposure (time above MIC) is also important for antimicrobial effect in the treatment of avian colibacillosis. 2 Thus, the requirement of PK/PD analysis has not been fully established, and further investigation is required to predict the efficacy of veterinary fluoroquinolones for the selection of the appropriate drug.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of fluoroquinolones against E. coli infections administered via drinking water has been reported for enrofloxacin in chickens (Bauditz, 1987) and turkeys (Behr et al, 1988;Hafez et al, 1990), for danofloxacin in chickens (Ter Hune et al, 1991), and for sarafloxacin in chickens and turkeys (Chansiripornchai and Sasipreeyajan, 2002). Under field conditions these fluoroquinolones can be applied to poultry with the drinking water in a flexible manner without compromising efficacy (Charleston et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy broiler chickens received bacitracin and lincomycin either alone or together showed non-significant elevation on bodyweight and weight gain but improved feed conversion rate throughout the experimental period when compared with the control group. The growth promoting the effect of antimicrobials may be due to suppression to the microorganisms that invade the host and retard its metabolic activity (Charleston et al 1998). Another explanation for improved body performance after using lincomycin and bacitracin is the antimicrobial effect of them which consequently improves the metabolic activity of bird by inhibiting pathogenic organisms that damage gut epithelium and impairing food absorption, inhibiting non pathogenic organisms which compete for growth factors in gut and inhibiting organisms producing toxic substances affecting growth (Abdelaziz 2002).…”
Section: Discussionmentioning
confidence: 99%